(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: Simulation of circular and square-shaped Silicon Carbide (SiC) diaphragm based pressure sensor and to study its deflection characteristics over a uniform pressure range of 0 to 200 kPa. Materials and Methods: COMSOL Multiphysics 5.6 is used for the simulation. Samples are divided into 2 groups, group 1 SiC circular diaphragm-based pressure sensor, and group 2 SiC square diaphragm-based pressure sensor with a pretest power of 80 %. Results: Square-shaped and circularshaped SiC diaphragm based pressure sensors exhibited displacement of 2.278 µm and 0.19874 µm respectively. On performing an independent sample t-test, the circular and square-shaped SiC-diaphragms exhibited the mean displacement values of 1.1390